La incidencia de los costos en la rentabilidad la "Cerrajería artística Soria" 2010 - Tipantuña, Guaman Ana Lucia (2012)
This research was done in the "Artistic Locksmith Soria", which is located in the City of La Maná province of Cotopaxi in Quito and Eugenio Espejo Street, just steps from the group Capelo and the Municipal Market, this idea came with the order to solve the problem of determining the actual cost of the product and know the profitability of these, starting from December 16, 2010 with the theme: "THE IMPACT OF COSTS IN THE PERFORMANCE OF" LOCKSMITH ARTISTIC SORIA " 2010, through various forms of analysis as applied in the thesis are: The cost to the structure of the "Artistic Locksmith Soria", costs of production by volume and by the costs of developing processes for different also known as products or production phases. According to the structure of the ironwork above, we analyzed the various elements of production such as raw materials, labor and manufacturing overhead, giving us as a result of cost of production in the period a value of 8.630,89 Usd, being in the raw material mostly reflected the value to 2.960,40 Usd, and also determined the unit cost of products and operating expenses was known they were part of manufacturing of products, which led me to establish the cost total production is 9.325,22 Usd. Within the volume of production was analyzed according to the variable costs of production volume up or down the total cost of the product and the fixed costs regardless of the quantity produced has remained stable in the application to the total cost, so that costs fixed are the different services, materials, wages, taxes, rents, interest, depreciation, etc., and variable costs are raw materials, labor and indirect materials that add value in fixed and variable costs 9.325,24Usd, the same that allowed us to determine the balance point of each product, with the metal door that should produce the greatest number of units (7 units) for the company to not lose or win. In the process costs, the locksmith has three phases of production are: Cut, Assembly and Finishing them that allow the owner to establish the individual cost of processes, giving a total production cost 8.630,89Usd, and Armed being that represented the highest value is 4.525,92 Usd. The State Income totaled determine that sales in the period is of 10,650.00 Usd, with a production cost of 8.630,89Usd, generating a net profit for the period 1.126,07 Usd. Profitability Analysis in a percentage allowed to observe the performance of the locks during the period, giving us the result that the return on sales is 10,57%, return on capital to 6,79% and return on the reversal of 13,05%. The hypothesis "The line of doors is the one that provides higher returns to the Art Hardware Soria in the period 2010," is rejected because the window line is the one that represents the highest percentage in profitability relative to sales, specifically the butterfly model with 4.67%.